2021
DOI: 10.1016/j.jds.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of the stress distribution in abutment teeth for connected crowns

Abstract: Background/purpose With the advancement of an over aging society, the average number of remaining teeth has increased. However, these remaining teeth do not always have sufficient alveolar bone support, and sometimes fabricated connected crowns are applied. This study evaluated the influence of crown material, crown thickness, and alveolar bone resorption on the stress distribution within the abutment teeth of connected crowns. Materials and methods Using structural ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Recent FEA modelling for implants with insufficient alveolar bone support has examined connected crowns, which can alleviate the stress concentrations at the margin of the crown and tooth [45]. Notably, PEEK is recommended as a long-term provisional crown material in cases where other auxiliary treatments are planned.…”
Section: Crownsmentioning
confidence: 99%
“…Recent FEA modelling for implants with insufficient alveolar bone support has examined connected crowns, which can alleviate the stress concentrations at the margin of the crown and tooth [45]. Notably, PEEK is recommended as a long-term provisional crown material in cases where other auxiliary treatments are planned.…”
Section: Crownsmentioning
confidence: 99%
“…Additionally, PEEK has garnered increasing interest in the biomedical field owing to its excellent biocompatibility, human bone-like elasticity, low plaque affinity, and minimal allergy-causing potential. 4 , 5 , 6 Furthermore, due to its other desirable properties, such as radiation transparency, PEEK is emerging as a promising substitute for metallic biomedical materials, particularly in dental applications. 7 , 8 Prior research has demonstrated that PEEK has been utilized in dental restorations, including crowns, implant abutments, and removable denture frameworks (such as clasps).…”
Section: Introductionmentioning
confidence: 99%